ANALYSIS OF RELATIONSHIPS BETWEEN MARKETING ECOSYSTEM PARTICIPANTS IN INDUSTRY CLUSTER (Marketing Journal, 2025)
This study analyzes the interrelations among participants in the marketing ecosystem within industrial clusters. It was found that intra -cluster interactions have a network -based structure, and synergistic efficiency is achieved through cooperation and kno wledge exchange. Social Network Analysis was used to assess participantsʼ centrality, while stakeholder analysis helped determine their roles and influence levels. A positive relationship between knowledge diffusion, innovation development, and cluster per formance was substantiated. Based on the findings, practical recommendations were developed for cluster management bodies and enterprises.
Keywords: industrial cluster; marketing ecosystem; social network analysis; stakeholders; knowledge exchange; synergy; innovation 592